2011
DOI: 10.5137/1019-5149.jtn.5039-11.1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low-dose radiation in the treatment of sciatic nerve injury in rats

Abstract: AIm: Peripheral nerve regeneration is often blocked by scar formation and misdirection of axon sprouts. The aim of this study is to evaluate electrophysiological and histopathological effects of low-dose radiation therapy on the prevention of intraneural scar formation in peripheral nerve injury. mAterIAl and methOds: In this experimental study, twenty rats were randomly divided into two groups. Left sciatic nerves were exposed and clipped by temporary aneurysm clip for 5 minutes in both groups. In all animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…1). 17,18 The site was rinsed with sterile saline solution, the muscle and skin layers were sutured with absorbable Vicryl 4-0 (Ethicon), and the wound was disinfected with Betadine (Mundipharma Medical, Hamilton, Bermuda). After 2 weeks, therapy was initiated as described earlier.…”
Section: Methodsmentioning
confidence: 99%
“…1). 17,18 The site was rinsed with sterile saline solution, the muscle and skin layers were sutured with absorbable Vicryl 4-0 (Ethicon), and the wound was disinfected with Betadine (Mundipharma Medical, Hamilton, Bermuda). After 2 weeks, therapy was initiated as described earlier.…”
Section: Methodsmentioning
confidence: 99%
“…In the treatment of peripheral nerve injuries, suturing with vinyl and silk was done first; however in light of the number of sutures and the negative effects of the sutures on recovery, fibrin glue and wrapping the injured nerve were also tried. Electrical stimulation, therapeutic ultrasound, low-dose radiation, and low-intensity laser were also tested in experimental models to produce nerve regeneration and functional recovery (8,13,15,16,17).…”
Section: I-light Microscopic Evaluationmentioning
confidence: 99%
“…Traffic accidents, firearm injuries, chemical injuries, cutting tool injuries, and crush traumas are some of the traumas that can be counted as the main causes ( 1 ). Although the most effective treatment after peripheral nerve trauma seems to be surgical repair (nerve anastomoses, flap, free-fat graft, and silicone cuffing), several healing-stimulating agents have been tested both in vitro and in clinical trials, although functional nerve regeneration with them has often been found insufficient ( 10 12 ). After inducing a sciatic nerve injury, functional response to medication can be evaluated by performing extremity changes and walking analysis in rats.…”
Section: Discussionmentioning
confidence: 99%